KERAGAAN PASAR KERJA PERTANIAN-NONPERTANIAN DAN MIGRASI DESA-KOTA: TELAAH PERIODE KRISIS EKONOMI - ADRIANI, DESSY (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The objectives of this research are: 1) to analyze factors effecting labor market performance; 2) to analyze factors effecting migration in Indonesia. The research used pooling data and be analyzed using simultaneous equation with 2 SLS technique. The result showed that labor force is influenced by productive-age population in both urban and rural area. In rural area, rural-urban migration also influenced labor force. Demand for labor is influenced by Gross Domestic Product, Labor Intensive Program in urban area, and Infrastructure Development Program for Developing Village in rural area. Labor productivity is influenced by sectoral real wage, calorie consumption and Social Safety Net Program for health sector. Sectoral real wage is influenced by Sectoral Minimum Wage and rate of inflation. The result also showed that sectoral real wage is not the important factor on labor market in Indonesia economic crisis.
Keywords: Rural, Urban, Labor Market, Migration